If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 + -1(-1x) = -20 + 5x + -7 Remove parenthesis around (-1x) 6x + 3 + -1 * -1x = -20 + 5x + -7 Multiply -1 * -1 6x + 3 + 1x = -20 + 5x + -7 Reorder the terms: 3 + 6x + 1x = -20 + 5x + -7 Combine like terms: 6x + 1x = 7x 3 + 7x = -20 + 5x + -7 Reorder the terms: 3 + 7x = -20 + -7 + 5x Combine like terms: -20 + -7 = -27 3 + 7x = -27 + 5x Solving 3 + 7x = -27 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 3 + 7x + -5x = -27 + 5x + -5x Combine like terms: 7x + -5x = 2x 3 + 2x = -27 + 5x + -5x Combine like terms: 5x + -5x = 0 3 + 2x = -27 + 0 3 + 2x = -27 Add '-3' to each side of the equation. 3 + -3 + 2x = -27 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = -27 + -3 2x = -27 + -3 Combine like terms: -27 + -3 = -30 2x = -30 Divide each side by '2'. x = -15 Simplifying x = -15
| 0=x^2-12x+32 | | 5x+14=78+3x | | -2*4= | | 3x-3=11x-67 | | x=57 | | r^3-3r^2+4=0 | | 5s^2+22s+21=0 | | 180-7x=38x+15 | | 3x-3=4x-1 | | 2x+28=10x-44 | | 5-2y=7 | | 6x+6=-144-9x | | 11x+5=6x+25 | | 3(2x+4)=48 | | -6=-3t^2+9t-.75 | | -6=-3t^2+9t-.075 | | x^2-8x=-10 | | 6e-7=21.8 | | x+3x=22 | | 7x+3=2(3x-2)+7 | | 2x-5=1/4+5x | | 7x^2-20x+12=0 | | 7x+3=2(3x-2)+8 | | 3x^3-3x^2+4x-4=0 | | -7(4x-8)=-28x+64 | | x^2-12x=-20 | | x^2-2=7 | | 8(2x-8)=2(8x+5) | | 6ac-3ad+8bc-4bd=0 | | 9+4x=42+x | | 5(2x-6)=10(x-3) | | x^6-2x^3-8=0 |